The Evolution of the Charge Transport Mechanism in Single‐Molecule Break Junctions Revealed by Flicker Noise Analysis. Issue 10 (19th December 2021) - Pan, Zhichao; Chen, Lichuan; Tang, Chun; Hu, Yong; Yuan, Saisai; Gao, Tengyang; Shi, Jie; Shi, Jia; Yang, Yang; Hong, Wenjing
Abstract: The electronic noise characterization of single‐molecule devices provides insights into the mechanisms of charge transport. In this work, it is reported that flicker noise can serve as an indicator of the time‐dependent evolution of charge transport mechanisms in the single‐molecule break junction process. By introducing time‐frequency analysis, the authors find that flicker noise components of the molecule junction show time evolution behavior in the dynamic break junction process. A further investigation of the power‐law dependence of flicker with conductance during the dynamic break junction process reveals that the mechanism of charge transport transits from the through‐space transport to the through‐bond transport, and is dominated by through‐space transport again when the junction is about to rupture. The authors' results provide a flicker noise‐based way to characterize the time‐dependent evolution of charge transport mechanisms in single‐molecule break junctions. Abstract : Flicker noise analysis is employed to study the evolution of charge transport mechanisms of single‐molecule junctions in break‐junction measurements. The authors find that the charge transport transits from through‐space transport to through‐bond transport in the opening process, and is dominated by through‐space transport when the junction is about to rupture.